PKM Pendampingan Penyusunan Modul Pembelajaran Berdiferensiasi dan Asesmen pada Kurikulum Merdeka untuk Meningkatkan Hasil Belajar - Mochamad Muchson; Susi Damayanti; Dian - Kusumaningtyas; Linda Rensy Widayani; Lucy Amelia (GUYUB: Journal of Community Engagement, 2023)
Assistance in preparing independent curriculum-based learning modules is needed by driving high schools to help compile the learning modules they carry out. This is because starting from the 2022/2023 academic year the government will implement a new national education curriculum known as the independent curriculum. Learning based on the Independent Curriculum emphasizes differentiated learning strategies which refer to the level of achievement or ability of students. This learning approach does not refer to class levels, but is grouped based on developmental phases or students' ability levels. Learning is adjusted to the achievements, level of ability, and needs of students, to achieve the expected learning outcomes or is student-centered. The independent curriculum applies differentiated learning, namely teaching at the right level, learning that considers student diversity so that teachers differentiate content, processes, learning outcomes and assessments. The method in this service includes a first stage of socialization which is then continued with mentoring for class X teachers at As-Syafiah Nganjuk Islamic High School and Nganjuk POMASDA High School. These two stages were packaged in the form of a workshop which was held in 5 meetings. The results obtained are teaching and learning modules that meet twice for all subjects in class X, totaling 18 subjects. The results obtained from this assistance are in addition to learning modules to assist teachers in carrying out the learning process to obtain maximum results. Because with the independent curriculum, it is seen that there is an increase in student learning outcomes in one semester.